2001
DOI: 10.1038/sj.bmt.1702784
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic stem cell transplantation for Diamond Blackfan anemia: a report from the Diamond Blackfan Anemia Registry

Abstract: Summary:The Diamond Blackfan Anemia (DBA) Registry of North America is a detailed database of patients with DBA from the United States and Canada. To date, 354 patients have been registered. From this database an analysis of the outcome of hematopoietic stem cell transplantation for DBA was undertaken. Of the 20 transplanted patients who met criteria for the diagnosis of DBA, eight underwent an allogeneic HLA-matched sibling hematopoietic stem cell transplant (SCT) and 12 an alternative donor SCT. The median a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 27 publications
2
59
0
3
Order By: Relevance
“…9 Current therapies include steroids and chronic transfusions, with the only definitive treatment being bone marrow transplantation. 15 Since the initial description in 1999 by Draptchinskaia, mutations in RPS19, RPS24, RPS17, and RPL35A have been identified in approximately one-third of patients with DBA. [16][17][18][19] More recently, Gazda et al identified mutations in RPL5 and RPL11 in an additional 11.4% of patients and noted that mutations in RPL5 were associated with a higher frequency of physical abnormalities, including cleft lip and/or palate, whereas mutations in RPL11 had more isolated thumb abnormalities compared with patients with mutations in RPS19.…”
Section: Diamond-blackfan Anemiamentioning
confidence: 99%
“…9 Current therapies include steroids and chronic transfusions, with the only definitive treatment being bone marrow transplantation. 15 Since the initial description in 1999 by Draptchinskaia, mutations in RPS19, RPS24, RPS17, and RPL35A have been identified in approximately one-third of patients with DBA. [16][17][18][19] More recently, Gazda et al identified mutations in RPL5 and RPL11 in an additional 11.4% of patients and noted that mutations in RPL5 were associated with a higher frequency of physical abnormalities, including cleft lip and/or palate, whereas mutations in RPL11 had more isolated thumb abnormalities compared with patients with mutations in RPS19.…”
Section: Diamond-blackfan Anemiamentioning
confidence: 99%
“…[1][2][3] Current therapies such as steroids, blood transfusion, and bone marrow transplantation often have severe side effects or are ineffective in many DBA patients. 1,[4][5][6][7][8] Approximately 40% of DBA patients have additional abnormalities that include short stature, cranofacial and urogenital malformations, heart defects and mental retardation. 1,8 DBA patients are also predisposed to develop acute myeloid leukemia, lymphoma and solid tumors.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 This can only be confirmed by determining the absence of a DBA-associated gene abnormality in the prospective related donor.…”
Section: Will Disease Management Be Influenced By the Results Of A Genmentioning
confidence: 99%